Numerical analysis on the reinforcement design of a granular strongly weathered rock slope based on in-situ direct shear test. Issue 2 (May 2021) - Li, Changchun; Lin, Qida; Lu, Weiping; Zhang, Zhichao
Abstract: It is difficult in the intact sampling of the granular strongly weathered rock of a slope by bench excavation, which will in turn influence the strength test results. In order to provide more accurate design parameters for the slope, its rock shear strength is analyzed by in-situ direct shear test, then the slope reinforced with different anchor frame beams are simulated by finite element method based on the strength parameters obtained from the in-situ direct shear test. The results show that the strength parameters of the granular strongly weathered rock are c=75.69 kPa and φ=35.23°. Reinforced with 1 ~ 4 layers of anchor frame beams, the maximum lateral displacement of the slope can be reduced by 30%, 47.6%, 53.5% and 53.5% compared with that of the unreinforced slope, respectively, which means that the deformation of the slope decreases with the increase of anchor frame beams. However, the fourth-layer anchor frame beam is not efficiency in the reinforcement. The maximum lateral displacement locates near the second excavation bench, which needs to be specially reinforced in the design.